Combining machine learning with Cox models to identify predictors for incident post-menopausal breast cancer in the UK Biobank - Liu, X; Morelli, D; Littlejohns, TJ; Clifton, DA; Clifton, L (Springer Nature, 2023)
We aimed to identify potential novel predictors for breast cancer among post-menopausal women, with pre-specified interest in the role of polygenic risk scores (PRS) for risk prediction. We utilised an analysis pipeline where machine learning was used for feature selection, prior to risk prediction by classical statistical models. An “extreme gradient boosting” (XGBoost) machine with Shapley feature-importance measures were used for feature selection among ≈ 1.7 k features in 104,313 post-menopausal women from the UK Biobank. We constructed and compared the “augmented” Cox model (incorporating the two PRS, known and novel predictors) with a “baseline” Cox model (incorporating the two PRS and known predictors) for risk prediction. Both of the two PRS were significant in the augmented Cox model (p<0.001 ). XGBoost identified 10 novel features, among which five showed significant associations with post-menopausal breast cancer: plasma urea (HR = 0.95, 95% CI 0.92–0.98, p<0.001 ), plasma phosphate (HR = 0.68, 95% CI 0.53–0.88, p=0.003 ), basal metabolic rate (HR = 1.17, 95% CI 1.11–1.24, p<0.001 ), red blood cell count (HR = 1.21, 95% CI 1.08–1.35, p<0.001 ), and creatinine in urine (HR = 1.05, 95% CI 1.01–1.09, p=0.006 ). Risk discrimination was maintained in the augmented Cox model, yielding C-index 0.673 vs 0.667 (baseline Cox model) with the training data and 0.665 vs 0.664 with the test data. We identified blood/urine biomarkers as potential novel predictors for post-menopausal breast cancer. Our findings provide new insights to breast cancer risk. Future research should validate novel predictors, investigate using multiple PRS and more precise anthropometry measures for better breast cancer risk prediction.